83 - FACTORS THAT AGRAVATE AND EASE CERVICALGIA: AN EVALUATION OF CONTEXT (Fiep Bulletin - online, 2011)
This study had the goal of evaluating which factors aggravate and which factors ease cervicalgia of individuals of both genders, between 30 and 50 years old, licensed by the INSS with diagnosis of cervical disc herniation. It was developed through an evaluation of context, with the physical functional vertebral spine evaluation method (Alexandre & Moraes, 2001) as the data collecting instrument, for the cervical region, concerning these factors. The results showed that 100% of the patients feel pain standing up, 95% report pain due to physical effort and sitting positions and 91% feel pain with any kind of movement. It was verified relief in 95% of the cases of rest, 91% with medicines e 77% with physical therapy, local heat and stretching exercises. It was concluded that the maintenance of given position and even, resting, for prolonged time, may worse cervicalgia and that the patients with this kind of pain, need to keep practicing daily life activities, seeking interdisciplinary, in which, the doctor, physical therapist and the physical education professional have essential roles.
Keywords: evaluation; cervicalgia; pain